Probiotics: Therapeutic Strategy on the Prevention and Treatment of Inflammatory Diseases: Obesity, Type 2 Diabetes Mellitus and Celiac Disease - dos Santos Pereira, Elisa; de Oliveira Raphaelli, Chirle; Massaut, Khadija B.; Ribeiro, Jardel Araújo; Soares Vitola, Helena Reissig; Pieniz, Simone; Fiorentini, Ângela Maria (Current Nutrition & Food Science, 2024)
Background: Recent evidence demonstrates the fundamental role of the gut microbiota in inflammatory diseases, and several mechanisms of action of probiotics in improvement of inflammatory parameters. Objectives: The objective of this review was to relate the consumption of probiotic bacteria and its effects on inflammatory diseases, including obesity, type II diabetes and celiac disease. Methods: A search was carried out in English, between the years 2011 and 2022, for research articles and clinical trials with humans and in vivo studies. Research showed improvement in cardiovascular risk markers, and improvement in insulin sensitivity, lipid profile and plasma atherogenic index, in obesity with the use of probiotics. In type II diabetes, decreased levels of fasting glucose, glycated hemoglobin, insulin and glycemic index, and increased levels of peptide 1, superoxide dismutase and glutathione peroxidase were observed. Results: In addition to cellular protection of the islets of Langerhans and positive alteration of TNF- α and IL-1β markers. Improvement in the condition of patients with celiac disease was observed, since the neutralization of the imbalance in serotonin levels was observed, reducing the expression of genes of interest and also, a decrease in cytokines. Conclusion: Therefore, the use of probiotics should be encouraged.
Keywords: islets of langerhans